Untreated bleeds in people with hemophilia A in a noninterventional study and intrapatient comparison after initiating emicizumab in HAVEN 1–3. Issue 6 (13th September 2022) - Callaghan, Michael U.; Asikanius, Elina; Lehle, Michaela; Oldenburg, Johannes; Mahlangu, Johnny; Uguen, Marianne; Chebon, Sammy; Kruse‐Jarres, Rebecca; Jiménez‐Yuste, Víctor; Shima, Midori; Trask, Peter; Kempton, Christine L.; et al.
Abstract: Background: Bleeding in people with hemophilia A can be life threatening, and intra‐articular bleeds can result in joint damage. Most clinical studies focus on treated bleeds, while bleeds not treated with coagulation factor(s) (untreated bleeds) are underreported. Objectives: We assessed the incidence of untreated bleeds during a noninterventional study (NIS) wherein people with hemophilia A, with or without factor VIII (FVIII) inhibitors, were managed according to standard practice. Patients/Methods: Using the Bleed and Medication Questionnaire, we prospectively collected data from three cohorts: Cohort A, adults/adolescents (age ≥12 years) with FVIII inhibitors; Cohort B, children (aged <12 years) with FVIII inhibitors; Cohort C, adults/adolescents without FVIII inhibitors. Untreated bleeds were analyzed for site, frequency, and etiology of bleeding and compared with those during emicizumab prophylaxis in the same individuals after transferring to a Phase III HAVEN trial. Results: In the 221 participants enrolled in the NIS (Cohort A, n  = 103; Cohort B, n  = 24; Cohort C, n  = 94), the incidence of untreated bleeds was approximately 40% of all bleeds in people with FVIII inhibitors and 26.2% in adolescents/adults without inhibitors. Approximately 70% of treated bleeds and approximately 54% of untreated bleeds in adults/adolescents were in joints. Untreated joint bleeds were less common (7.1%) in children. Overall, intra‐individual comparisons showed reduced treated/untreated bleeds following transition from standard to emicizumab prophylaxis. Conclusion: A significant proportion of bleeding events are untreated in people with hemophilia A. There is a need to further understand why bleeds remain untreated and to capture such events in clinical studies.